2015
DOI: 10.1038/bjc.2015.220
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 mutations sensitize to chemotherapy in patient-derived pancreatic cancer xenografts

Abstract: Background:Germline mutations of the BRCA tumour suppressors have been associated with increased risk of pancreatic cancer. Clinical evidence suggests that these patients may be more sensitive to treatment with cisplatin. As the frequency of germline BRCA mutations is low, definitive experimental data to support the clinical observations are still missing.Methods:We tested gemcitabine and cisplatin sensitivity of four BRCA1 and BRCA2 mutant and three BRCA1 and BRCA2 wild-type (WT) patient-derived pancreatic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 25 publications
4
53
1
1
Order By: Relevance
“…The third model, OCIP28, is derived from a patient with a germline BRCA2 mutation and is highly sensitive to gemcitabine as previously reported. 26 There was a modest, non-significant reduction in the growth of this model treated with MK-1775 alone, which might be linked to a recently-suggested role for Wee1 in homologous repair, 6,13 but similar to the other 2 models, and in contrast to an earlier paper, 15 we did not see strong evidence for a synergistic interaction between the 2 drugs. Treatments were well tolerated in the mice, with no significant loss of body weight (Fig.…”
Section: Effects Of Mk-1775 In Combination With Gemcitabinecontrasting
confidence: 56%
“…The third model, OCIP28, is derived from a patient with a germline BRCA2 mutation and is highly sensitive to gemcitabine as previously reported. 26 There was a modest, non-significant reduction in the growth of this model treated with MK-1775 alone, which might be linked to a recently-suggested role for Wee1 in homologous repair, 6,13 but similar to the other 2 models, and in contrast to an earlier paper, 15 we did not see strong evidence for a synergistic interaction between the 2 drugs. Treatments were well tolerated in the mice, with no significant loss of body weight (Fig.…”
Section: Effects Of Mk-1775 In Combination With Gemcitabinecontrasting
confidence: 56%
“…Lohse et al (24) identified that BRCA1 and BRCA2 mutant xenografts were significantly more sensitive to cisplatin compared with the control, while the BRCA1 and BRCA2 wild type models exhibited sensitivity to gemcitabine but not to cisplatin. However, BRCA1 expression was significantly decreased in the HCT-8 cells compared with in the drug-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical models using PDAC cell lines as well as patient-derived murine xenografts have shown that tumor BRCA2 deficiency was significantly associated with sensitivity to DNA cross-linking agents (such as platinum salts), as well as radiation therapy compared with BRCA2 proficiency (Porcelli et al 2013, Andrei et al 2015, Lohse et al 2015. In addition to case reports (Sonnenblick et al 2011), several retrospective case series have described marked efficacy of platinum salts in BRCA2 mutation carriers with advanced PDAC (Lowery et al 2011, Golan et al 2014, Luo et al 2015, Vyas et al 2015.…”
Section: Use Of Cross-linking Cytotoxic Agents In Brca2 Mutation Carrmentioning
confidence: 99%